Finite-Time Identification Algorithm based on Time-Varying Homogeneity and Lyapunov Approach*. Issue 18 (2016) - Ríos, H.; Efimov, D.; Moreno, J.A.; Perruquetti, W.
Abstract: In this paper the problem of time-varying parameter identification is studied. To this aim, an identification algorithm is developed in order to identify time-varying parameters in a finite-time. The convergence proofs are based on a notion of finite-time stability over finite intervals of time, i.e. Short-finite-time stability; homogeneity for time-varying systems; and Lyapunov function approach. The algorithm asks for a condition over the regressor term which is related to the classic identifiability condition corresponding to the injectivity of such a term. Simulation results illustrate the feasibility of the proposed algorithm.